Yield of dry matter and nutritive quality of the pasture Brachiaria brizantha x Brachairia ruziziensis cv. Mulato in the CautoValley, Cuba - Ram?rez, J. L.; Herrera, Rafael Segundo; Leonard, I.; Verdecia, D.; ?lvarez, Y. (Cuban Journal of Agricultural Science, 2010)
The influence of the regrowth age (30 to 105 d in the rainy season and dry season) and the climate factors on the yield of dry matter and the nutritive quality of the pasture Brachiaria brizantha x Brachairia ruziziensis cv. Mulato were assessed in a random block design with four replicates. The trial was developed on a fluvisol type soil in dry conditions and without fertilization. The DM yield was increased significantly up to 90 d (P < 0.001), and quadratic equations were fitted to the DM yield and the age in both seasons. Crude protein and DM and OM digestibility decreased with age (P < 0.001), and equations of quadratic regression were fitted to these variables and age. The highest percentages were noted at the age of 30 d in both seasons. NDF, ADF, lignin, and cellulose were increased with age (P < 0.001). The highest values were noted at 105 d of regrowth in both seasons, and the equations of quadratic regression of these variables were fitted to age. It may be concluded that age and the edaphoclimatic conditions had marked effect on the performance of the indicators assessed by decreasing the nutritive quality in the rainy season, and the yield in the dry season. Further studies on the performance of these chemical composition indicators are recommended. Key words. Brachiaria, chemical composition, digestibility, climatic factors.